2020
DOI: 10.1186/s12909-020-02049-w
|View full text |Cite
|
Sign up to set email alerts
|

Communication skills of medical students: survey of self- and external perception in a longitudinally based trend study

Abstract: Background: As good communication skills are crucial for doctor-patient interactions, it is recommended to incorporate them in medical school programs from the very beginning. On this basis medical schools in Germany introduced the OSCE (objective structured clinical examination) to examine and by this foster learning of communication skills as assessment drives learning. The aim of the study was to examine the development of the communication skills of medical students during an OSCE to investigate how commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…However, it is clear that the communication skills of residents are lacking. Previous research has reported differences between self and patient perceptions of physicians' communication skills (31). This comparison is lacking in the current work and is one of its limitations.…”
Section: Discussionmentioning
confidence: 82%
“…However, it is clear that the communication skills of residents are lacking. Previous research has reported differences between self and patient perceptions of physicians' communication skills (31). This comparison is lacking in the current work and is one of its limitations.…”
Section: Discussionmentioning
confidence: 82%
“…(28) Interestingly, a study by Graf and colleagues described that communication skill training had improved the students' self-con dence over seven semesters, but that external ratings (standardized patients) of their communicative skills showed a decline. (29) Lastly and not unexpectedly, con dence scores in resolving or negotiating con icts were relatively low. Although, during the classes on diversity, we try and provide starting doctors with tools to help them deal with issues arising from differences in cultures, religions and norms and values, where in the simulation we confront them with an angry or aggressive patient, it requires encounters in clinical practice to further develop this skill.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, a study by Graf and colleagues described that communication skills training had improved the students’ self-confidence. However, this increase in self-confidence didn’t correlate with the external rating (by patients) of their communicative skills, showing again the importance of skill rating [ 24 ]. As a side note, we would like to emphasize that our study focuses purely on the communicative aspect of ACP and the communicative skills involved.…”
Section: Discussionmentioning
confidence: 99%